The use of sodium lamps for low-intensity laboratory safelighting for optical dating - Spooner, N. A.; Questiaux, D. G.; Aitken, M. J. (Ancient TL, 2000)
The choice of laboratory illumination for use with optical dating samples involves a compromise between minimising the unwanted bleaching of light-sensitive signals while providing sufficient visibility to allow efficient and safe workplace practice. Described here is a laboratory safelight fulfilling these requirements. The safelight module consists of a low-pressure sodium vapour lamp enclosed within a filtered and shuttered housing, and provides lowintensity (< 1 µW/cm2) yellow-orange light, predominantly from the well-known 589.0 and 589.6 nm sodium D-lines.